Outcome assessment of the implementation of Mass Drug Administration against lymphatic filariasis in Kalaburagi (Gulbarga) Karnataka, India: A cross-sectional survey - Puttamaligaiah Subhas Babu; Bhoompuram Nagaraja Goud; Shambhulinga B Kambale (Journal of Vector Borne Diseases)
Background & objectives: Mass Drug Administration (MDA) of Di-Ethyl Carbamazine and Albendazole is an effective strategy recommended by the World Health Organization to prevent transmission and eliminate lymphatic filariasis. Under the National Vector Borne Disease Control Programme (NVBDCP) in India, MDA is carried out as a yearly activity in endemic areas to accelerate the progress towards elimination of lymphatic filariasis. The study was carried with the objective to determine the coverage of MDA against lymphatic filariasis among the eligible population in Kalaburagi district, Karnataka and delineate the common reasons for non-acceptance of MDA. Methods: Field-based cross-sectional survey was carried out. Cluster sampling of 4 clusters (3 rural and 1 urban) from four different taluks (one cluster from each taluk) of the district reporting high, medium and low coverage of MDA (as reported by District Malaria Office) Members from selected households in all clusters were interviewed regarding MDA administration, directly observed treatment, side effects and any co morbidities which ruled out MDA administration. Responses documented as tally marks in assessment sheets shared by NVBDCP office. Proportions, frequencies, and mean were calculated and inferential statistics were used. Results: A total of 1263 individuals were assessed for MDA from a total 240 households (60 households in each cluster). The coverage of MDA varied from 90.33% in Heerapur in Kalaburagi Urban to 97.87% in Mogala thanda (Chittapur Taluk). Interpretation & conclusion: MDA Coverage against lymphatic filariasis has improved when compared to previous studies and it has also exceeded the coverage threshold as determined by programme for elimination of lymphatic filariasis.